1975
DOI: 10.1007/bf01317436
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the activity of small molecular interferon inducers: Tilorone and acridine drugs

Abstract: The antiviral activity and induction of interferon-like substance by mepacrine (quinacrine, Atabrine) and Acranil in mice, described previuosly, was studied in more detail and compared with tilorone. The serum substance induced by Acranil was characterized as mouse interferon. Acranil, given parenterally, proved to be as strong as tilorone regarding interferon stimulation, in spite of the presence of only one side chain in the Acrainl molecule. Mepacrine was found to be a wealer interferon inducer than either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The results so far have not yielded a more active compound. Other synthetic inducers that have been reported include anionic polymers (28,36,106,125), tilorone (30,58,91), cationic dyes (57), and propane-.diamine (75).…”
Section: Production Of Interferonmentioning
confidence: 99%
“…The results so far have not yielded a more active compound. Other synthetic inducers that have been reported include anionic polymers (28,36,106,125), tilorone (30,58,91), cationic dyes (57), and propane-.diamine (75).…”
Section: Production Of Interferonmentioning
confidence: 99%
“…In our study, the existence of the antiviral effect of Tilorone and Cridanimod was confirmed, including the protection from lethal infection in mice (expectedly) and the ability to reduce viremia in rats (less expectedly). The doses in our study are equivalent to the recommended human therapeutic doses, and they represent the lower end of a range of doses in the literature because the majority of papers describe effects at higher dosages (100–250 mg/kg Tilorone, or >300 mg/kg Cridanimod to mice, per os) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%